Avaliação do desempenho de três sistemas fotovoltaicos, sendo um estático e dois móveis, rotacionados em um plano e dois planos. - Debastiani , Gilson (2022)
The generation of electricity from water origin, predominantly used in Brazil, is being cyclically impacted by climate change, where increasingly severe droughts, combined with increased electricity consumption, cause risks of lack of electricity. These risks, in turn, are minimized by the activation of thermoelectric plants, which require high operating costs and contribute to the increase in Greenhouse Gases (GHG). The solar resource has high levels of availability in practically the entire Brazilian territory and is contributing to the significant increase in the share of solar energy in the national electricity matrix. However, the form of incidence of solar radiation on the photovoltaic module directly affects the performance of the system. The hypothesis is that, with the implementation of solar, daily and seasonal tracking systems, in addition to positively affecting energy generation, it can also impact solar and thermal irradiance variables differently in each system, which can affect efficiency of these. In this context, the general objective of the work was to dimension, install and evaluate each of the three proposed arrangements, aiming to obtain the best cost benefit ratio, both in the installation and in the useful production of electric energy, in the city of Cascavel/PR. A bibliographic research was carried out, aiming to survey the available tracking systems, with their advantages and disadvantages, which guided the definition of the arrangements to be used. Subsequently, three photovoltaic systems, independent thermal and electrical sensors, and meteorological sensors were installed. With them, it was possible to quantify their values and determine the performance of each arrangement. Among the main results obtained, we highlight the equality between the average values of solar irradiance in all arrays, by irradiance range; the number of HSPs between Arrangements 3 and 2, and between Arrangement 1 and the horizontal surface incidence; all module temperatures, according to the criteria for evaluating the irradiance bands and all the efficiencies by time band, where there is also equality between Arrangements 1 and 2 and between Arrangements 1 and 3. The efficiency of the systems, by solar irradiance band , for Arrangement 1 (7.27%), Arrangement 2 (10.38%) and Arrangement 3 (12.73%), had different means, with a significance of 5%. The cost of generated energy presented values of R$ 0.11/kWh, R$ 0.19/kWh and R$ 0.22/kWh for Arrangement 1, Arrangement 2 and Arrangement 3, respectively.